Nursery crown budding technique in rubber (Hevea brasiliensis) to overcome major leaf diseases - Philip, S.; Prem, E.E.; Idicula, S.P. (PLACROSYM XXV: Building Smart & Resilient Farming and Systems Approaches for Prosperity in Plantation Crops Sector, 12-14 December 2023, ICAR-Indian Institute of Oil Palm Research, Pedavegi, Eluru, Andhra Pradesh, p. 135.)
Plant disease control using chemicals is the most effective, short-term disease management strategy practiced for most of the agricultural crops. Environmental concerns, shortage of plant protection chemicals, higher price and the unavailability in the markets, labour scarcity are constrains of chemical control of diseases. Climate change and prolonged rains have increased disease incidence and widespread leaf fall is observed in rubber plantations in many regions. Outbreak of two new diseases viz. New colletotrichum circular leaf spot (CCLS) and Thread blight was observed in rubber plantations recently. In this situation it is very essential to find out sustainable alternate methods to avoid repeated spraying of chemicals in the plantations to control various diseases. Crown budding is a technique in which the crown of a high yielding clone is modified by developing a canopy with high disease tolerance. This is accomplished by budding at 8-10 feet height with a disease tolerant clone. It is also considered as a three-part tree with a root stock from seed, high yielding trunk and disease tolerant canopy of another clone developed through crown budding. Experimental plants of the clone PB 260 were raised in 65x35 cm polybags for 18 -20 months till the plants attained adequate height. Budding with disease tolerant clone FX 516 was undertaken at 10 feet height just below the top whorl having matured leaves. After successful budding, plants were taken to field at one whorl stage after cutting the top leaving a snag (12 cm) above the bud and planted in the rainy season. The crown budding success was > 85% and field establishment was > 95%.Budded plants of the same clone and same age without crown budding were planted as experimental control. Three hundred crown budded plants were maintained in the field, which attained tappable girth in the seventh year. Disease severity was monitored under unsprayed conditions both in crown budded and control plants. Intensity of Colletotrichum leaf disease, Powdery mildew and Abnormal leaf fall (ALF) was monitored. Uniform tapping system (1/2 S, D3) was employed in crown budded and control plants. Monthly yield recording, annual girth increment and tapping panel dryness (TPD) were recorded. No major disease incidence except that of mild powdery mildew diseases was noticed on the plants. The tapping panel dryness in both crown bud and control trees were recorded in A and B panel. The TPD incidence in crown budded plants is comparable to control. Crown budded trees recorded an yield improvement up to 30 per cent over control. Latex properties of the crown budded trees were comparable to control. Once a successful crown budding was established in the field with high yielding trunk and disease tolerant crown (FX 516), the spraying against ALF/CCLS and dusting against powdery mildew disease can be avoided, thus reducing the cost of plant protection and also minimizing the environmental pollution.
Keywords: Nursery crown budding; FX 516